Employment Status of Women in the Seafood Processing Sector of Gujarat - Jeyanthi, P.; Gopal, Nikita; Murty, L. N.; Geethalakshmi, V. (Fishery Technology, 2025)
More than 75% of the workforce in the seafoodprocessing sector in India are women. This studyexplored the employment status of women in seafoodprocessing sector in Gujarat, which is one of thelargest states in terms of number of seafood processingplants and quantity of seafood exports. The maleto female ratio in the industry was 1:1.74 and 1:1.66in the contractual and permanent employment categoriesrespectively. About 63% of the respondentswere under 30 years of age and unmarried. Themonthly wages of women workers at the floor levelwas ` 2594/- which is much lower than the minimumwages prescribed by the Gujarat State for unskilledworkers which is ` 214.90 day-1. It was observed thatthe major determinants of women’s employment inthe sector were their educational status and wages.The wage of worker in processing sector showedsignificant positive relationship with age, educationand work experience.